Weathering-Induced Strength Degradation and Hydro-Mechanical Controls on the Stability of Multilayered Tropical Rock Slopes - Stephanie Ivy Luna; Hideki Shimada; Takashi Sasaoka; Akihiro Hamanaka (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Tropical environments accelerate rock weathering, which can significantly reduce the stability of mineralized slopes. This study investigates the influence of weathering and groundwater conditions on the stability of a strong–weak–strong multilayered rock slope hosting an iron deposit in the Philippines, where intense rainfall and highly fractured rock masses are common. Detailed geological and hydrogeological investigations were conducted to construct two-dimensional numerical models of the slope system. Mechanical characterization of both weathered and unweathered rock masses was performed using field hardness testing and laboratorygeomechanical tests. These parameters were incorporated into numerical simulations to evaluate slope stability under varying degrees of weathering, weak-layer thickness, and hydrological conditions derived from developed phreatic surfaces. Results indicate that when the middle weak layer is thin, a 50% weathering intensity still allows a stable multilayered slope at an Overall Slope Angle (OSA) of 60°. However, as weak-layer thickness increases, the same weathering degree leads to slope instability. Weathering effects recorded at theinvestigated study area correspond to an average reduction of 10.8 units in the Geological Strength Index (GSI), and are equivalent to a 50% weathering degree, implying that each 0.2 reduction in GSI represents approximately 1% weathering of the rock mass. Considering weathering-induced strength degradation, the optimally safe slope angle decreases from the originally designed 60° to approximately 35°, maintaining a minimum factor of safety of 1.2. Although the stabilizing effect of other countermeasures was excluded from this study. Hydrological analysis further reveals that low rainfall may temporarily increase slope stability due to matric suction induced by capillary effects in clay-like mineral sericite, although prolonged rainfall generates positive pore pressures that reduce stability. The thickness of the weak layer also produces localized increases in hydraulic gradient due to permeability contrasts, increasing susceptibility to rainfall-induced failure. These findings highlight the importance of quantitatively incorporating weathering and hydrogeological effects in slope design for tropical open-pit mines.